A Novel Bioimpedance-Based Detection of Miltefosine Susceptibility Among Clinical Leishmania donovani Isolates of the Indian Subcontinent Exhibiting Resistance to Multiple Drugs - Ghosh, Souradeepa; Biswas, Souvik; Mukherjee, Sandip; Pal, Arijit; Saxena, Aaditya; Sundar, Shyam; Dujardin, Jean-Claude; Das, Soumen; Roy, Syamal; Mukhopadhyay, Rupkatha; Mukherjee, Budhaditya (Frontiers in Cellular and Infection Microbiology, 2021)
The extent of susceptibility towards miltefosine (Mil), amphotericin B (AmpB), and paromomycin (Paro) was measured among 19 clinical isolates of Leishmania donovani (LD). Thirteen of these clinical isolates were reported to exhibit low susceptibility towards sodium stibogluconate (SSG-R), while six of them were highly susceptible (SSG-S). The degree of clearance of amastigotes (EC50) for these predefined SSG-R- and SSG-S-infected macrophages was determined against Mil, AmpB, and Paro. Two out of the 13 SSG-R isolates (BHU575 and BHU814) showed low susceptibility towards all three drugs studied, while the rest of the 11 SSG-R isolates showed varying degrees of susceptibility either towards none or only towards individual drugs. Interestingly, all the SSG-S isolates showed high susceptibility towards Mil/AmpB/Paro. The total intracellular non-protein thiol content of the LD promastigotes, which have been previously reported to be positively co-related with EC50 towards SSG, was found to be independent from the degree of susceptibility towards Mil/AmpB/Paro. Impedance spectra analysis, which quantifies membrane resistance, revealed lower impedimetric values for all those isolates exhibiting low efficacy to Mil (Mil-R). Our analysis points out that while non-protein thiol content can be an attribute of SSG-R, lower impedimetric values can be linked with lower Mil susceptibility, although neither of these parameters seems to get influenced by the degree of susceptibility towards AmpB/Paro. Finally, a correlation analysis with established biological methods suggests that impedance spectral analysis can be used for the accurate determination of lower Mil susceptibility among LD isolates, which is further validated in the LD-infected in vivo hamster model.